Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Lesbian literature a third world feminist perspective - Moraga, Cherrie; Smith, Barbara (The Radical Teacher, 2014)
"A Baseline From Which to Build a Political Understanding: The Background and Goals of the Course."Barbara Smith: I'd taught Black women's literature, interdisciplinary courses on Black women and talked about Lesbianism as an "out" lesbian in my "Introduction to Women's Studies" courses, but I really wanted to do a Lesbian lit course. Lesbian literature had never been offered by the Women's Studies program at the University of Massachusetts in Boston, although the program is almost ten years old. There was a gay literature course that had been co-taught by a gay man and a lesbian, but its orientation was quite a bit different from what I had in mind.
Keywords: approches et analyses; féminisme décolonial; histoire et politique; lesbianisme; littérature; personnes lesbiennes; pédagogie; ressource en ligne; thématiques

Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Section: 288 pages : illustrations ; 22 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis